Analysis of chemical characteristics, flavonoids, and organoleptics on shallot skin (Allium cepa) kombucha - Desvy Pebiyanti; Rahma Widiantie; Agus Prianto (STKIP Persada Khatulistiwa Sintang, 2021)
Shallots (Allium cepa) is an important aromatic plant, with a level of consumerity that is directly proportional to the increase in shallot skin waste. Whereas the skin of shallots contains flavonoids (quercetin) that are 3-5 times higher than the tubers. This research focuses on the use of shallot skin ingredients fermented by Symbiotic Culture of Bacteria and Yeast (SCOBY) into kombucha drinks. With the aim to explore the influence of long fermentation of shallot skin kombucha on the parameters of the chemical characteristics of pH and Total Titrable Acid (TTA); the presence of flavonoids; and organoleptic flavors, colors, aromas. The result is the length of fermentation affecting the decrease in the pH value, and had a very noticeable effect on the increase in the Total Titrable Acid value. Flavonoids were qualitatively tested by 3 reagents (10% NaOH, AlCl3 1%, H2SO4 judging by discoloration. At show all samples show positive results of flavonoid presence. The length of fermentation for organoleptic assessment has a significant effect on taste and aromas, but has no significant effect on the kombucha color. The recommendation for a good fermentation time with high acceptance is 8 days of fermentation.